Open access, virtual science libraries, geospatial analysis and other complementary information and communications technology and science, technology, engineering and mathematics assets to address development issues, with particular attention to education (UN New York, 2012)
Provides an overview of how open access, virtual science libraries and geographic information systems could be harnessed to address development challenges, especially in the area of education.
Keywords: EDUCATION